A purple acid phosphatase, GmPAP33, participates in arbuscule degeneration during arbuscular mycorrhizal symbiosis in soybean. (5th March 2019) - Li, Chengchen; Zhou, Jia; Wang, Xiurong; Liao, Hong
Abstract: Arbuscules are the central structures of the symbiotic association between terrestrial plants and arbuscular mycorrhizal (AM) fungi. However, arbuscules are also ephemeral structures, and following development, these structures are soon digested and ultimately disappear. Currently, little is known regarding the mechanism underlying the digestion of senescent arbuscules. Here, biochemical and functional analyses were integrated to test the hypothesis that a purple acid phosphatase, GmPAP33, controls the hydrolysis of phospholipids during arbuscule degeneration. The expression of GmPAP33 was enhanced by AM fungal inoculation independent of the P conditions in soybean roots. Promoter‐β‐glucuronidase (GUS) reporter assays revealed that the expression of GmPAP33 was mainly localized to arbuscule‐containing cells during symbiosis. The recombinant GmPAP33 exhibited high hydrolytic activity towards phospholipids, phosphatidylcholine, and phosphatidic acid. Furthermore, soybean plants overexpressing GmPAP33 exhibited increased percentages of large arbuscules and improved yield and P content compared with wild‐type plants when inoculated with AM fungi. Mycorrhizal RNAi plants had high phospholipid levels and a large percentage of small arbuscules. These results in combination with the subcellular localization of GmPAP33 at the plasma membrane indicate that GmPAP33 participates in arbuscule degeneration during AM symbiosis via involvement in phospholipid hydrolysis. Abstract : GmPAP33 participates in arbuscule degeneration during AM symbiosis via involvement in phospholipid hydrolysis in soybean. The recombinant GmPAP33 exhibited high hydrolytic activity towards phospholipids. Mycorrhizal RNAi plants had high phospholipid levels and a large percentage of small arbuscules.